El material concreto como recurso didáctico para fortalecer el aprendizaje de los recursos naturales, en los estudiantes de noveno grado de educación general básica, paralelo “A”, del colegio “PíoJaramillo Alvarado” de la ciudad de Loja. Periodo académico 2013-2014 - Mejía Quizhpe, Cecilia Noemí (2015)
Natural resources are addressed in the Natural Sciences which is the set of basic science devoted to the study of nature , such as chemistry, physics, biology among the most relevant Natural resources make up the foundation of life , based on this requires that elementary school students recognize the importance they aim to preserve and protect them. For these and other reasons, the use of teaching materials in the techniques of teaching - learning become key for strengthening educational processes. I think it important , that the proposed topic ; the concrete material in the classroom is set up as an educational resource of great importance in strengthening the knowledge of natural resources. Its function is to allow the student to experience the concept from the stimulation of the senses, making getting to internalize the concepts that want to teach from the manipulation of objects in their environment. The research aims to study " The particular material as a teaching resource to enhance learning of natural resources , in the ninth grade students of Basic General Education, parallel to the College " Pio Jaramillo Alvarado "in the city of Loja period 2013-2014 academic " The overall objective is : Apply the concrete material as a teaching resource to enhance learning of natural resources in the ninth grade students of Basic General Education, parallel to , the school " Pio Jaramillo Alvarado " in the city of Loja academic period 2013-2014 In the development of research takes account of the following methods : the analytical , descriptive, inductive, deductive and method of Pearson linear correlation . As the survey technique was used and as a tool for information gathering questionnaire. In the analysis, discussion and interpretation of the data it is found that students do not have a clear conception about the definition , importance and classification of natural resources , thereby determining a basic learning; so it is I could see that the importance is not given to using concrete materials such as ; sheets sequences , photographs, collage, paintings, among others (see development of research ) to address issues related to natural resources such as: definition, importance , classification, among others